Population structure and growth of the hermit crab Pagurus brevidacylus (Anomura : Paguridae) from the northern coast of São Paulo, Brazil - Mantelatto, F. L.; Christofoletti, R. A.; Valenti, Wagner Cotroni [UNESP] (Cambridge University Press, 2005)
The hermit crab Paguras brevidactylus (Crustacea: Anomura: Paguridea) from the infralittoral area of Anchieta Island, Ubatuba, was characterized by population Structure (size, sex ratio, reproduction and recruitment) and growth. Animals were collected monthly during 1999 by SCUBA diving. A total of 1525 individuals was collected (633 males and 892 females), 695 of them were ovigerous females. Overall sex ratio was 0.7:1 in favour of females. The crabs showed a unimodal distribution with males significantly larger than females. Ovigerous females were collected during all months and in high percentages from 1.0 mm of shield length, demonstrating intense and Continuous reproduction. The longevity was approximately 24 months for males and 18 for females, which showed larger growth rate and reached sexual maturity earlier (two months) than males. The low number of males in this Population may be due to the longer life span. Moreover, the sexual dimorphism favours males during the intra- and interspecific fights by shell, food, reproduction and territory. Females demonstrated a short life cycle and intense reproduction.